Management of "difficult asthma" - Bel, Elisabeth (Henry Stewart Talks, 2011)
Difficult asthma and severe refractory asthma, Heterogeneous reasons for severe asthma, "High dose" therapy, Treatments for severe asthma, Eosinophilic vs. non eosinophilic inflammation, Effect of CRS treatment on asthma, Mechanism of action of anti IgE, Effect of anti IgE on severe asthma exacerbations, Effect of anti IL-5 (mepolizumab) on spontaneous asthma exacerbations, Clarithromycin in neutrophilic asthma, Macrolides in chronic stable asthma, Mechanisms of asthma severity in obese patients, Implications for the future